Renal Dysfunction in Patients with Left Ventricular Assist Device - Lamees I. El Nihum; Nina Manian; Priya Arunachalam; Qasim Al Abri; Ashrith Guha (Methodist DeBakey Cardiovascular Journal)
Late-stage heart failure and renal dysfunction are often seen in conjunction. Cardiorenal syndrome (CRS) describes the complex interaction between the two disease states. Early literature described the pathophysiology of CRS as related only to reduced cardiac output and decreased renal perfusion. Recent literature suggests a more multifaceted mechanism. Left ventricular assist devices (LVAD), used as bridge-to-transplant and destination therapy in patients with heart failure, impact not only cardiac function but also renal function, especially in those patients with preoperative renal dysfunction. The mechanism by which LVAD implantation affects renal function is complex and understated in early literature. In this review, we discuss the pathogenesis of CRS, the impact of preoperative renal dysfunction in patients undergoing LVAD implantation, and the effect of LVAD implantation on postoperative renal function.